Dissecting Major Signaling Pathways throughout the Development of Prostate Cancer - Henrique B. da Silva; Eduardo P. Amaral; Eduardo L. Nolasco; Nathalia C. de Victo; Rodrigo Atique; Carina C. Jank; Valesca Anschau; Luiz F. Zerbini; Ricardo G. Correa (Prostate Cancer)
Prostate cancer (PCa) is one of the most common malignancies found in males. The development of PCa involves several mutations in prostate epithelial cells, usually linked to developmental changes, such as enhanced resistance to apoptotic death, constitutive proliferation, and, in some cases, to differentiation into an androgen deprivation-resistant phenotype, leading to the appearance of castration-resistant PCa (CRPCa), which leads to a poor prognosis in patients. In this review, we summarize recent findings concerning the main deregulations into signaling pathways that will lead to the development of PCa and/or CRPCa. Key mutations in some pathway molecules are often linked to a higher prevalence of PCa, by directly affecting the respective cascade and, in some cases, by deregulating a cross-talk node or junction along the pathways. We also discuss the possible environmental and nonenvironmental inducers for these mutations, as well as the potential therapeutic strategies targeting these signaling pathways. A better understanding of how some risk factors induce deregulation of these signaling pathways, as well as how these deregulated pathways affect the development of PCa and CRPCa, will further help in the development of new treatments and prevention strategies for this disease.